High Level Bioaerosol Protection against Infective Aerosols: How Medical Face Masks Compare against Respirators - Christian M. Sterr; Aline Dick; Lena Schellenberger; Julian Zirbes; Claudia Nonnenmacher-Winter; Frank Günther (Canadian Journal of Infectious Diseases and Medical Microbiology)
Face masks and respirators are commonly used to prevent the transmission of infectious diseases that spread by respiratory droplets and aerosols. However, there is still uncertainty about the protective effect of the different types of masks against virus containing aerosols. To determine the as-worn bioaerosol protection efficacy of different face coverings and estimate the possible protective function against airborne diseases, we challenged different respirators and medical masks on a standardized dummy head with a bioaerosol containing MS2 bacteriophages as virus surrogates. In our experiments, FFP2 respirators showed the highest filtration efficacy 94 ± 4 (SD) % followed by medical masks 93 ± 3 (SD) % and KN95 respirators 90 ± 7 (SD) %. Nevertheless, we found no statistically significant difference between respirators and medical masks in terms of provided protection against infective aerosols. Our findings indicate that both respirators and medical masks provide a high as-worn bioaerosol protection efficacy against virus containing aerosols, and therefore, a very high protection against airborne diseases. Considering the higher comfort, better availability, and lower price of medical masks in contrast to respirators, it is recommendable to use medical face masks especially in low risk situations and in general public.